Predicting Risk Behaviors in Adolescents Through Social Isolation and Negative Self-Talk - Kraus, Sabine; Torres, Jennifer; Batthyany, Karina (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective:  This study aimed to investigate the predictive roles of social isolation and negative self-talk in adolescent risk behaviors.Methods and Materials: The research employed a correlational descriptive design involving 377 high school students from the United States, selected using stratified random sampling based on the Morgan and Krejcie sample size table. Standardized instruments were used to measure the dependent variable (risk behaviors) and the independent variables (social isolation and negative self-talk). Data collection was conducted through self-report questionnaires, and statistical analyses were performed using SPSS version 27. Pearson correlation was used to assess the bivariate relationships between variables, and a standard linear regression analysis was conducted to evaluate the combined and individual predictive power of the independent variables on risk behaviors.Findings: The results revealed significant positive correlations between both social isolation and risk behaviors (r = .41, p < .001), and negative self-talk and risk behaviors (r = .53, p < .001). Linear regression analysis indicated that both social isolation (β = .29, p < .001) and negative self-talk (β = .42, p < .001) were significant predictors of adolescent risk behaviors, with the model explaining approximately 38% of the variance in the dependent variable (R² = .38, F(2, 374) = 113.82, p < .001). Among the two predictors, negative self-talk had the stronger standardized beta coefficient, indicating a higher contribution to risk behavior variance.Conclusion: The findings suggest that both social isolation and negative self-talk significantly contribute to adolescent risk behaviors, with cognitive self-perceptions playing a particularly prominent role. These results underscore the importance of early intervention targeting adolescents’ social connectedness and internal dialogue to prevent engagement in harmful behaviors.